Theory of Virtual Genre Studies: The Problem of Methodology - Tyukaeva Nadezhda (Виртуальная коммуникация и социальные сети, 2025)
The article addresses terminological and methodological challenges in the linguistics of digital communication. Its primary aim is to introduce the concept of web-idiom as a systemic language variant of the internet environment, encompassing stable grammatical, lexical, and pragmatic patterns adapted to digital spaces (platforms, algorithms, multimodality). The novelty of the study lies in overcoming the polysemy of existing terms and developing a hierarchical model language → web-idiom → web-sociolect, where web-sociolects (e.g., TikTok idiom, Discord slang) are interpreted as platform-conditioned linguistic systems. The empirical base of the article includes 120 works on virtual genres and genre studies (scientific articles, monographs, dissertations, as well as 500 digital texts (comments, posts, streams, memes). Grounded in K. R. Popper’s methodological nominalism, the author proposes a shift from an essentialist paradigm to a functional one, emphasizing the explanatory function of theory over descriptive taxonomy. A paradigmatic crisis in virtual genre studies stems from the dominance of a priori nominations (blog, meme) and the absence of verifiable models. The web-genre source studies require an interdisciplinary approach that integrates corpus linguistics, digital anthropology, and data science to analyze communicative strategies and cultural codes. The term web-idiom ensures taxonomic precision by distinguishing digital language forms from offline categories. The concept of web-genre source studies establishes a framework for descriptive practices, overcomes their cyclical nature, and forms a corpus of primary and secondary texts. It focuses on typical phenomena in net-idioms and subsequent theoretical exploration of how web-genres structure digital discourse. Future research prospects include the integration of quantitative methods and practical validation of models in communication studies and linguistic expertise. The study contributes to the theory of speech genres by providing tools to analyze the dynamics of internet communication amid technological transformation.